Beyond the Energy Gap Law: The Influence of Selection Rules and Host Compound Effects on Nonradiative Transition Rates in Boltzmann Thermometers. Issue 11 (7th April 2022) - Netzsch, Philip; Hämmer, Matthias; Turgunbajew, Erich; van Swieten, Thomas P.; Meijerink, Andries; Höppe, Henning A.; Suta, Markus
Abstract: Apart from the energy gap law, control parameters over nonradiative transitions are so far only scarcely regarded. In this work, the impact of both covalence of the lanthanoid–ligand bond and varying bond distance on the magnitude of the intrinsic nonradiative decay rate between the excited 6 P5/2 and 6 P7/2 spin–orbit levels of Gd 3+ is investigated in the chemically related compounds Y2 [B2 (SO4 )6 ] and LaBO3 . Analysis of the temperature‐dependent luminescence spectra reveals that the intrinsic nonradiative transition rates between the excited 6 P J ( J = 5/2, 7/2) levels are of the order of only 10 ms −1 (Y2 [B2 (SO4 )6 ]:Gd 3+ : 8.9 ms −1 ; LaBO3 :Gd 3+ : 10.5 ms −1 ) and differ due to the different degree of covalence of the GdO bonds in the two compounds. Comparison to the established luminescent Boltzmann thermometer Er 3+ reveals, however, that the nonradiative transition rates between the excited levels of Gd 3+ are over three orders of magnitude slower despite a similar energy gap and the presence of a single resonant phonon mode. This hints to a fundamental magnetic dipolar character of the nonradiative coupling in Gd 3+ . These findings can pave a way to control nonradiative transition rates and how to tune the dynamic range of luminescent Boltzmann thermometers. Abstract : It is more than just the energy gap: In this work, it is demonstrated that the nonradiative coupling between electronic 4f n levels of the lanthanoid ions follows selection rules similarly to radiative transitions. It is also shown that the covalence of the lanthanoid–ligand bond can have a little impact on the nonradiative transition rate using Gd 3+ .